IMPLEMENTASI METODE COLLISION DETECTION PADA GAME WASIOR ADVANTURE MENGGUNAKAN CONSTRUCT 2 - Krisnawati, Ela; Ardhianto, Eka (Information Technology and Telematics, 2018)
ABSTRACT Game is one means to refresh the mind after a variety of routines that make fatigue, especially for those who need entertainment and limited time is expected this game in addition to be a means of refreshing also makes an option to improve agility in learning. This study aims to create a kind of Arcade Game that adventure genre with a short level, easy control, varied characters and increasing difficulty level. The research method used in this research is using coliision detection. The results of the study is a game that is expected to be entertainment and learning media for game users.